Compliant gluten-free children with celiac disease: an evaluation of psychological distress - Martorana Serena; Lionetti Elena; Guarnera Manuela; Spina Massimo; Reale Laura; Mazzone Luigi; Mazzone Domenico (BMC, 2011)
Abstract Background Children with chronic illnesses are known to have increased risks for emotional and behavioral problems. In the present study, children and adolescent suffering from celiac disease (CD) were compared with healthy controls to assess differences in the psychological profile. Methods A total of 100 well-treated and compliant CD patients (65 females/35 males; age mean ± SD: 10.38 ± 2.71) were compared to 100 normal controls (58 females/42 males; age mean ± SD: 11.47 ± 2.61). Emotional and behavioral problems were assessed by the Child Behavior Checklist (CBCL), the Children's Depression Inventory (CDI) and the Multidimensional Anxiety Scale for Children (MASC). Results Subjects with CD self-reported an increased rate of anxiety and depression symptoms and showed higher scores in "harm avoidance" and "somatic complaints", in the CBCL parent-report questionnaire, as compared to healthy control subjects. Furthermore, gender differences could be observed in the group of CD patients, with males displaying significantly higher CBCL externalizing scores, in social, thought and attention problems, as compared to female, who in turns showed more prominent internalizing symptoms such as depression. Conclusions The increased rate of emotional and behavioral problems in children and adolescent with CD emphasizes the importance of an early detection of mental health problems in these children.